Recovery from Conflict : Lessons of Success - Mueller, Hannes; Piemontese, Lavinia; Tapsoba, Augustin (World Bank, Washington, DC, 2017)
This paper studies long-term impacts of violent conflict, to provide insights into the costs of conflict and policies to prevent conflict relapse. The findings link evidence on the contemporaneous effects of conflict with its persistent impact, especially by combining multiple data sources such as night lights, indicators of political exclusion, and nutrition. There is a strong level effect on output arising from the intensity of conflict, which, contrary to perceptions of post-conflict booms, on average is not reversed by subsequent more rapid growth. The paper investigates two possible channels that make conflict persistent: refugee flows and investment. Both channels display wide variation across recovery episodes, and are capable of large surges, which can in some cases generate rapid recoveries. Where recoveries lack buoyancy --which is the case for many post-conflict episodes -- deeper political constraints appear to be at work, which may ultimately relate to the effectiveness of power sharing. Finally, to highlight the need for more effective policies and knowledge in this area, the paper shows that the human development costs of conflict are huge, and can persist through a full generation. Policy recommendations and pointers for future research form the conclusion.